Cakes and Breads in Oribasius’ Collectiones medicae - Jagusiak, Maciej Kokoszko, Zofia Rzeźnicka, Krzysztof (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
Oribasius (4th century A.D.), Greek doctor, created at least four medical works. The most important of them is Collectiones medicae. We are going to present two foods described there: cakes and breads based on cereal products, described in the beginning of the 1st book. For ancient Mediterranean societies cereals were food which constituted the staple of the diet for the overwhelming majority of the population.